Tanzania-the Darling of the Donor Community? a critical review of the failure of past development aid efforts - Lynge, Kristina (Saarbrucken Lambert, 2011)
Tanzania remains one of the world's poorest countries, with a per capita GNI of US
Includes bibliographies
Keywords: Tanzania